Methylprednisolone-Responsive Leptospiral Acute Pulmonary Syndrome: A Case Report - Iman D. Johan-Arief; Shen H. Lee; Xin Y. Er; Ganesh Kasinathan; Naganathan Pillai (University Library System, University of Pittsburgh, 2015)
Background: Leptospirosis is an infectious disease caused by the spirochete of the genus leptospira. It is thought to be the most common zoonosis globally and has a wide range of clinical presentations with pulmonary hemorrhage being one of its most severe manifestations. This entity known as acute pulmonary syndrome carries a high fatality rate. However, it can be effectively managed with methylprednisolone therapy. Case: We report a case of leptospirosis in a 26-year-old Bangladeshi male who was otherwise healthy. He presented with a 7-day history of fever with chills and rigors, and hemoptysis for a duration of 2 days. Physical examination revealed a febrile and lethargic man. Respiratory examination exhibited bilateral generalized crepitations over the lung fields. A chest radiograph performed showed bilateral alveolar shadowing. The diagnosis of leptospirosis was made based on positive Immunoglobulin M enzyme-linked immunosorbent assay serology, which was then confirmed by the microscopic agglutination test for leptospirosis. The patient was commenced on intravenous antibiotics and methylprednisolone at this time. He responded well clinically with resolution of fever and hemoptysis and a marked decrease in crepitations upon auscultation. This correlated with radiological improvement evidence by an obvious reduction in alveolar shadowing on subsequent chest radiograph 2 days later. Conclusion: This case is highly pertinent to the medical field as leptospirosis is an ever-growing problem and acute pulmonary syndrome is an emerging manifestation of it. Therefore, early recognition and intervention is required as this can be effectively treated with methylprednisolone therapy even in resource-limited settings